A flexible anisotropic self-powered piezoelectric direction sensor based on double sided ZnO nanowires configuration. (13th February 2015) - Nour, E S; Chey, C O; Willander, M; Nur, O
Abstract: We have successfully synthesized highly dense and well aligned zinc oxide nanowires (NWs) on the two sides of a PEDOT: PSS substrate by a single step low temperature hydrothermal method. The grown sample was used to fabricate a double sided piezoelectric nanogenerator (NG). The maximum harvested output power density from the fabricated double sided NG configuration was about 4.44 mW cm −2 . The results obtained from the present double sided NG were approximately double the output from a single side. In addition to that, the voltage polarity of the harvested voltage from the two sides of the NG has been investigated. The results showed that upon bending, an anisotropic voltage polarity is generated on the two sides. Indicating that, this double sided NG can be used as a self-powered voltage polarity based direction sensor. The results of the present flexible double sided NG is very promising for harvesting energy from irregular mechanical energy sources in the surrounding environment. In addition, the fabricated configuration showed stability for sensing and can be used in surveillance and security applications.